Bridging the Skills Gap: The Impact of Internal Quality Assurance on Educational Outcomes - Sitti Hardiyanti Arhas; Nasir Nasir; Jamaluddin Jamaluddin; Arismunandar Arismunandar (Lembaga Bale Literasi, 2025)
This study aims to analyze the impact of internal quality assurance systems in bridging students’ skill gaps in vocational education. A qualitative approach with a case study design. Data were collected through interviews, documentation, and surveys, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that the internal quality assurance system has been implemented across all stages of the quality cycle, including standard setting, quality mapping, planning, implementation, and monitoring and evaluation. However, the implementation remains largely procedural and has not been fully integrated to produce optimal educational outcomes. Students demonstrate adequate technical skills, yet still face limitations in non-technical skills such as communication, adaptability, and problem-solving. These gaps are attributed to the suboptimal use of data in decision-making, limited involvement of industry stakeholders, and the underdeveloped quality culture within schools. This study concludes that internal quality assurance contributes to improving educational processes but has not been fully effective in bridging students’ skill gaps. Therefore, strengthening the integration of the quality cycle, adopting data-driven approaches, and enhancing collaboration with industry are essential to improve the relevance and quality of educational outcomes.